2022
DOI: 10.1002/pc.26864
|View full text |Cite
|
Sign up to set email alerts
|

Temperature analysis in fiber metal laminates drilling: Experimental and numerical results

Abstract: Drilling process of fiber metal laminates (FML) requires a proper design of the processing parameters to prevent the occurrence of several issues and minimize defects, which can be detrimental for the integrity of the parts. These aspects become more critical in dry machining used in aeronautic field. In this scenario, the monitoring of process temperature is crucial to obtain useful information for machining optimization since many critical factors, such as matrix burnout, fiber pull‐out and delamination, dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Sorrentino et al [ 58 ] reported that high-speed cutting and low-feed machining allow a significant reduction of the F z component of the cutting force, which is responsible for any delamination/detachment issues in the material. Additionally, a decrease in spindle speed and high feed rate in the drilling of GLARE composite causes tool tip temperature, which causes problems of higher cutting force and critical resin temperature in polymeric composite materials [ 59 , 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…Sorrentino et al [ 58 ] reported that high-speed cutting and low-feed machining allow a significant reduction of the F z component of the cutting force, which is responsible for any delamination/detachment issues in the material. Additionally, a decrease in spindle speed and high feed rate in the drilling of GLARE composite causes tool tip temperature, which causes problems of higher cutting force and critical resin temperature in polymeric composite materials [ 59 , 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…In most of the literature AA 2024-T3 has been used for the fabrication of FMLs. 7,[32][33][34][35][36][37][38][39] Few of the researchers have also used other grades of aluminum alloys such as AA 1050, [40][41][42] AA 1060-H12, 43 AA 1200-H14, 44 AA 2024-O, 45 AA 5005, 46 AA 5052-O, 47 AA 5052-H32, [48][49][50] AA 6061-T6, 17,29,51,52 AA 6063-T6, 53 and AA 7075-T6. 52,54,55 Limited amount of work has been conducted on the Magnesium alloy, 56,57 Titanium, 45 and Steel.…”
Section: Research Gap Addressed In the Papermentioning
confidence: 99%
“…On a component level application, Wang et al 31 established a multi‐objective integrated optimization framework considering for the fabrication of a tapered rim composed of CFRP rim and aluminum alloy spoke. In most of the literature AA 2024‐T3 has been used for the fabrication of FMLs 7,32–39 . Few of the researchers have also used other grades of aluminum alloys such as AA 1050, 40–42 AA 1060‐H12, 43 AA 1200‐H14, 44 AA 2024‐O, 45 AA 5005, 46 AA 5052‐O, 47 AA 5052‐H32, 48–50 AA 6061‐T6, 17,29,51,52 AA 6063‐T6, 53 and AA 7075‐T6 52,54,55 .…”
Section: Research Gap Addressed In the Papermentioning
confidence: 99%
“…The thermophysical properties of fiber-reinforced polymers result in high temperatures at the tool tip during the drilling process. [31][32][33] These materials have relatively low thermal conductivity and heat capacity compared to metal matrix materials, causing an imbalance in the energy transfer between the tool and workpiece. Additionally, their low thermal expansion coefficient leads to accuracy errors during machining.…”
Section: Introductionmentioning
confidence: 99%
“…The dry drilling process poses a risk of inducing thermal damage because of elevated process temperatures. The thermophysical properties of fiber‐reinforced polymers result in high temperatures at the tool tip during the drilling process 31–33 . These materials have relatively low thermal conductivity and heat capacity compared to metal matrix materials, causing an imbalance in the energy transfer between the tool and workpiece.…”
Section: Introductionmentioning
confidence: 99%